Good Character, Good Deeds and Good Speech for Developing Multicultural Islamic Education: An Islamic Concept - Muhtar Arifin Sholeh, Muhammad; Waston,; Nirwana AN, Andri; Hidayat, Syamsul (Multicultural Islamic Education Review, 2023)
This research is qualitative research that aims to develop an Islamic quality-of-life model for Islamic multicultural education. Research is conducted by referring to various sources of writing (literary research), and then formulating with deductive and inductive reasoning (thinking). The four criteria for a successful life (luck, win), namely faith, good deeds, correctness, and patience. These four criteria constitute a unified whole, and should not be broken down or reduced. The word 'sholih' means 'whole' (not broken apart) or 'complete', which is also usually translated as 'good'. Goodness due to wholeness and completeness. Wholeness and completeness in the concept of "Amal Sholih" include amal imaniah (faithful action), amal ilmiah (scientific action), amal karimah (noble action), amal rahmah (beloved action), amal barakah (better action), amal salamah (safe action), and amal kamilah (complete action). Faithful action is the action that must be based on faith, namely the six pillars of faith. Scientific action is an action that contains knowledge. Amal karimah is human deeds that show good deeds. Beloved action is the action that reflects rahmah (compassion, love), which arises from a clean conscience. Better action is a human action that provides benefits and added value (added goodness) to others and oneself. Safe action is the act of human beings who are safe and save themselves and others in this world and the hereafter. Complete action is the human action that fulfills 100% of the target.